Atividade mandioqueira em brejo de altitude : o caso do município de Água Branca no alto Sertão de Alagoas - Santos, Fábio Pereira dos (2023)
Cassava (Manihot Esculenta Crantz) is cultivated by small peasant farmers in more than 100 tropical and subtropical countries around the world. Its adaptability to different climates, soils, drought tolerance and sporadic pest attacks make cassava a viable productive alternative for developing countries. According to FAO (2013), cassava roots are rich in carbohydrates, which makes them a surplus source of energy. This tuber feeds around 1 billion people in the world, especially in lower-income countries. The uses attributed to cassava are diverse: in human food, animal feed and industry. This work's main objective is to study the agrarian space of Água Branca city in the state of Alagoas (AL) in order to understand the various aspects that configure the process of territorialization of municipal cassava activity. To support the analysis of the work, the historical dialectical method was adopted. Different methodological procedures were used: bibliographical research, secondary data collection and field research. The latter included reconnaissance of the study area, interviews with peasant cassava producers, owners of flour mills and middlemen, in addition to photographic recording, including the use of drones. The dissertation is structured into four chapters and final considerations. The first chapter deals with the theoretical questions that guided our research. We use two main concepts, namely: space and territory. In the second chapter, we addressed the territorial formation of the State of Alagoas, Alto Sertão and the municipality of Água Branca. We also carry out a general characterization of the municipality of Água Branca-AL, presenting socioeconomic and also physical data. We rescued the historical process of occupation of this space, we seek to highlight the importance of indigenous and quilombola peoples in the formation of this territory. The third chapter is dedicated to discussions about the peasantry and the cassava activity developed in Água Branca-AL. We seek, through classic and contemporary authors, to locate what peasantry is, and also its importance in the field nowadays. In the fourth chapter, research data is presented. We begin with a general characterization of the territory researched (Serra do Cavalo and Preguiçoso) for this we present the socioeconomic data, as well as, we analyze the profile of the peasant production units and the profile of the peasants who are dedicated to cassava activities. Next, we analyze the production and commercialization process of cassava flour. Finally, we analyze the techniques and technologies used in the peasant production of cassava flour. It was found that there was a timid modernization of cassava activity in Água Branca-AL, however, insufficient to increase cultivation and processing into flour, causing the seasonal migration of peasant producers to the sugarcane fields in the south of Alagoas and Sergipe and also for the harvest of coffee in the Southeast region. The research carried out showed the role of the peasantry in the agrarian space of Água Branca and how cassava activity has been fundamental to the permanence of this form of social and productive organization.